Pembinaan Sistem Akuntansi Serta Pelaporan Keuangan di SMK Kolese Tiara Bangsa - Syahril Effendi; Tukino Tukino; Ronald Wangdra; Yvonne Wangdra; Baru Harahap (LPPM Universitas Putera Batam, 2023)
Effective accounting and financial reporting systems are crucial for ensuring transparency, accuracy, and the sustainability of finances in vocational schools like SMK Kolese Tiara Bangsa. This research aims to examine the efforts in fostering and enhancing the accounting and financial reporting systems at SMK. The study involves data collection from various sources, including interviews with administrative staff, document analysis, and monitoring of accounting procedures. The research findings indicate that SMK Kolese Tiara Bangsa has undertaken significant efforts to improve their financial governance. These efforts include training for administrative staff, the utilization of state-of-the-art accounting software, and enhancing understanding of applicable accounting standards. Furthermore, the school has also revamped their financial reporting processes, encompassing the regular preparation of financial statements and strict budget monitoring. The improvement in the accounting and financial reporting system has aided SMK Kolese Tiara Bangsa in more effectively managing their finances, enhancing the accuracy of financial information, and increasing transparency and accountability. This study provides valuable insights into the importance of fostering and developing accounting systems in educational institutions, with the hope of setting an example for similar institutions aiming to improve their financial management.